2019
DOI: 10.1111/jocn.14758
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying, biased behaviours and performance review in the nursing profession: A qualitative study

Abstract: Aims and objectives To explore staff nurses’ discourses of workplace bullying, to critically examine how these discourses affect their responses to bullying. Background Workplace bullying has been identified as a pervasive problem within the nursing profession. Efforts to eradicate workplace bullying need to involve staff—targets as well as bystanders. By understanding how this population conceptualises workplace bullying, more effective and targeted solutions to the problem can be devised. Design This qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
(82 reference statements)
1
9
0
6
Order By: Relevance
“…This reframing of the problem by management occurred through the creation of a discourse that placed employee resistance as professional incompetence, thus linking the narrative to professional identity and performance management [76]. This has been observed in other studies with regard to employee resistive actions to bullying [77,78] but the scale of this was notable in this study. Furthermore, it is interesting that the reframing brought the issue into the realm of individual performance management and assessment.…”
Section: Reframing Of Complaints: 'It's Not Us It's You'supporting
confidence: 69%
“…This reframing of the problem by management occurred through the creation of a discourse that placed employee resistance as professional incompetence, thus linking the narrative to professional identity and performance management [76]. This has been observed in other studies with regard to employee resistive actions to bullying [77,78] but the scale of this was notable in this study. Furthermore, it is interesting that the reframing brought the issue into the realm of individual performance management and assessment.…”
Section: Reframing Of Complaints: 'It's Not Us It's You'supporting
confidence: 69%
“…Thus, early identification in the professional practice environment can offer subsidies to health service managers for the development of prevention and control programs of this behavior in health institutions (6) . Efforts to combat bullying at work among nurses and staff need to include training in legitimate methods of performance analysis, workshops on how to interact with various co-workers, and examining how nursing teaching practices contribute to the perpetuation of bullying in clinical settings (9) .…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, a phenomenon that has been present for many years in nursing work environments and that has plagued the health of professionals worldwide, often veiled or remaining only as an index for situational diagnosis (1,9) .…”
Section: Introductionmentioning
confidence: 99%
“…However, Jeong and Kim's (2018) study showed that emotion-oriented strategy was one of the factors related to the intention to leave the workplace. Seeking peer support could be a strategy to express negative feelings and obtain support, but it could not change the negative context in which the phenomenon occurred because they did not know how to intervene (Johnson 2019). This creates a climate of frustration that affects the entire organization: previous research has shown that witnesses to workplace aggression perceived more stress and had more mental health problems than nonwitnesses (Sprigg et al 2019;Acquadro Maran et al 2021).…”
Section: Discussionmentioning
confidence: 99%